Analisis Semiotika Charles Sanders Peirce Postingan Mural Banksy pada Media Sosial Instagram - Ilham Almahli, Moch; Fanaqi, Chotijah; Hendrawan, Heri (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Criticism and freedom of speech that builds important information for society can now take a visual form such as mural art. One of the famous mural artists who dares to convey information by using meaning signs and messages such as criticism in his mural artwork is Banksy. One of his famous murals raises the issue of natural destruction. This research uses Charles Sanders Peirce's Semiotics Theory which is famous for its triadic model analysis, namely the representamen, object, and interpretant. And using data collection techniques in the form of observation and interviews. The result of the research shows that the meaning and message contained in Banksy's mural contains information from colors, images, and shapes in detail about how he can convey messages about criticism of the government and people who do not care about environmental sustainability. And also so that people can pay more attention to environmental sustainability so that there is no damage to nature due to human actions themselves.